2021
DOI: 10.33963/kp.15696
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 1283 alleviates cardiomyocyte damage caused by hypoxia /reoxygenation via targeting GADD45A and inactivating the JNK and p38 MAPK signaling pathways

Abstract: Background Clarifying the molecular mechanism and identifying markers of myocardial ischemia / reperfusion injury is crucial for the treatment of acute myocardial infarction. aims This study aimed to investigate the roles and underlying regulatory mechanisms of microRNA 1283 (miR-1283) and GADD45A in cardiomyocytes injured by hypoxia / reoxygenation (H / R). methods Bioinformatic analyses were used to determine the expression of GADD45A and miR-1283 based on various datasets from the Gene Expression Omnibus da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We identified some miRNAs including hsa-miR-1283, hsa-miR-664b-3p, hsa-miR-579-3p, which targeted multiple regions in the RdRp sequence of BCoV, SARS-CoV, and SARS-CoV-2, these miRNAs have been previously linked with onco-protective roles, indicating their growth regulatory function. For example, hsa-miR-1283 has been linked with cardio-protection and inhibition of apoptosis (Liu et al , 2021), thereby blocking oncogenesis. In addition, this miRNA has also been implicated in hypertension (Chen et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We identified some miRNAs including hsa-miR-1283, hsa-miR-664b-3p, hsa-miR-579-3p, which targeted multiple regions in the RdRp sequence of BCoV, SARS-CoV, and SARS-CoV-2, these miRNAs have been previously linked with onco-protective roles, indicating their growth regulatory function. For example, hsa-miR-1283 has been linked with cardio-protection and inhibition of apoptosis (Liu et al , 2021), thereby blocking oncogenesis. In addition, this miRNA has also been implicated in hypertension (Chen et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We identified some miRNAs including hsa-miR-1283, hsa-miR-664b-3p, hsa-miR-579-3p, which targeted multiple regions in the RdRp sequence of BCoV, SARS-CoV, and SARS-CoV-2; these miRNAs have been previously linked with onco-protective roles, indicating their growth regulatory function. For example, hsa-miR-1283 has been connected with cardio-protection and inhibition of apoptosis (Liu et al, 2021), thereby blocking oncogenesis. In addition, this miRNA has also been implicated in hypertension .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have focused on how to prevent or reduce myocardial injury. Many studies have found that cell‐derived exosomes can carry and transfer myocardial protective miRNAs into damaged cardiomyocytes and have the beneficial effect of cardiac protection 11,12 . They play a critical role in the myocardial injury repair process, but the specific regulatory mechanism of miRNAs in AMI remains unclear.…”
Section: Discussionmentioning
confidence: 99%